Histopathological study for using of pox inactivated vaccine in goats (Mongolian Journal of Agricultural Sciences, 2015)
This study used goat pox inactivated vaccine (serial No.57,58, year of 2014 ) produced at Biocombinat State Owned Enterprise (SOE).On day 21 and at 1, 3, 6, 9, 12 months after vaccination, the vaccinated animals are challenged with a virulent “Ho” strain by subcutaneous inoculation with 0.1 ml (10-3.5).We have evaluated that the goat pox inactivated vaccine is effective for up to 6 months.Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 51-55